Effect of mixing Mach number and mixing efficiency on the preliminary cycle design of mixed high-BPR turbofans. (May 2019) - Cleton, Bjorn; Anselmi, Eduardo; Pellegrini, Alvise; Pachidis, Vassilios; Laskaridis, Panagiotis
Highlights: Mixing effectiveness and Mach number at the mixer inlet influences thrust gain. These parameters have an interconnected and opposite effect on thrust gain. Both parameters strongly influences optimum FPR. Mach number at the mixer inlet directly affect the engine size. Engine size limitations constrain the potential thrust gain achievable. Abstract: This article presents the implementation of an updated analytical flow mixing model in a state-of-the-art, non-dimensional gas turbine cycle performance simulation and optimisation tool. The model considers three separate streams in the mixer, each expanding through its own 'virtual' nozzle. The use of three streams, compared to one single stream, allows for a more realistic simulation of a mixed exhaust gas turbine. This approach is used in a parametric study to assess the effect of the choice of mixing efficiency and mixer inlet Mach number on the preliminary design of mixed-exhaust, high-bypass ratio turbofan engines. It was found that in terms of best thermal performance, a trade-off exists between mixer inlet Mach number and mixer effectiveness. The findings of this research establish some useful guidelines for the accurate selection of these two parameters to achieve robust cycle designs.